2016
DOI: 10.1021/acsami.6b08954
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of the Microstructure and Interfacial Properties of PIMs/ZIF-8 Mixed Matrix Membranes

Abstract: A study integrating advanced experimental and modeling tools was undertaken to characterize the microstructural and interfacial properties of mixed matrix membranes (MMMs) composed of the zeolitic imidazolate framework ZIF-8 nanoparticles (NPs) and two polymers of intrinsic microporosity (PIM-1 and PIM-EA-TB). Analysis probed both the initial ZIF-8/PIM-1 colloidal suspensions and the final hybrid membranes. By combination of dynamic light scattering (DLS) and transmission electron microscopy (TEM) analytical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
87
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 60 publications
12
87
1
2
Order By: Relevance
“…One way to stabilize the polymer matrix is by introducing several different kinds of fillers to design mixed matrix membranes (MMMs). Main examples for fillers that are used for MMMs are porous materials like MOFs, [101][102][103] carbon nitrides 104 but also microporous polymer networks [105][106][107] and related molecular fillers like organic cages (Fig. 6).…”
mentioning
confidence: 99%
“…One way to stabilize the polymer matrix is by introducing several different kinds of fillers to design mixed matrix membranes (MMMs). Main examples for fillers that are used for MMMs are porous materials like MOFs, [101][102][103] carbon nitrides 104 but also microporous polymer networks [105][106][107] and related molecular fillers like organic cages (Fig. 6).…”
mentioning
confidence: 99%
“…However, several studies have revealed that ZIF‐8 nanocrystals tend to form agglomerates in MMMs at relatively high loadings (>20 wt%), which may result in the formation of nonselective voids that can deteriorate the membrane selectivity. [20,23a,24] Moreover, strong interactions between ZIF‐8 fillers and polymer matrix, which are important for improved interfacial compatibility, have not been widely observed in MMMs yet . Diverse strategies, including ammonia modification, polymer coating, and polymer grafting, haven been demonstrated to be effective in enhancing polymer–ZIF interfacial compatibility, which can improve the comprehensive performance of MMMs for separations.…”
Section: Choices Of Advanced Porous Materialsmentioning
confidence: 99%
“…The same group [104] also examined ZIF-8/PIM-1 membranes using molecular simulations and experiments. Their results showed that the microstructure of MMMs is based on many features including the molecular structure and rigidity of polymer and MOF/polymer interactions.…”
Section: Understanding the Mof/polymer Compatibility: The Role Of Commentioning
confidence: 99%